Overlapping holoprosencephaly‐polydactyl syndrome and asphyxiating thoracic dystrophy, an incidental finding in late prenatal ultrasound: A rare case report - Sereke, Senai Goitom (Clin Case Rep, 2021)
Holoprosencephaly‐polydactyly syndrome and asphyxiating thoracic dystrophy rarely overlap but if they do, they have poorer prognosis. Early prenatal detection of multiple congenital anomalies plays a crucial role in the management of pregnancy.